Morphological and Ultrastructural Characterization of Antennal Sensilla and the Detection of Floral Scent Volatiles in Eupeodes corollae (Diptera: Syrphidae) - Dong, Wan-Ying; Wang, Bing; Wang, Gui-Rong (Frontiers in Neuroanatomy, 2021)
The olfactory sensing system of the syrphid fly Eupeodes corollae is essential in pollination and prey localization, but little is known about the ultrastructural organization of their olfactory organs. In this study, the morphology, distribution, and ultrastructural organization of antennal sensilla of E. corollae in both sexes were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Neuronal responses of a subtype of sensilla basiconica to floral scent compounds were recorded by single sensillum recording (SSR). Ten morphological types, including Böhm bristles, sensilla chaetica, microtrichiae, sensilla trichodea, sensilla basiconica, sensilla clavate, sensilla coeloconica, sensilla styloconica, sensilla placodea, and sensory pit, were identified. Except for Böhm bristles and sensilla chaetica, which were distributed on the scape and pedicel of E. corollae antennae, innervated sensilla were densely distributed on the flagellum, a vital sensory organ. Further, observing ultrastructural organization showed that the sensilla trichodea, basiconica, and clavate are single-walled with multiple nanoscale pores perforating the cuticle. Sensilla coeloconica are double-walled and have no wall pores, but instead, have longitudinal grooves along with the pegs. Sensilla chaetica, Böhm bristles, and microtrichiae did not have wall pores on the cuticle or sensory cells at the base. The SSR results indicated that neuron B housed in the subtype of sensilla basiconica I (SBI) mainly responded to methyl eugenol and other aromatic compounds. Overall, our results provide valuable information to understand the morphology and ultrastructure of antennal sensilla from E. corollae. These findings are beneficial for the studies of the neuronal function map of olfactory sensilla and for determining evolutionary relationships in Diptera.